Brand Equity Notebook Berdasarkan Atribut: Studi Komparatif Atas Acer, Asus, HP dan Toshiba - , Andi Rahmat Hia, Dr. Ike Janita Dewi, MBA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Formulation of the problem in this study were: a). What attributes of the brand image forming notebook b). How brand image of the Acer, Asus HP and Toshiba notebook, which is the market leader and How is the relative position of the brand image of some of the brand notebook c). Does Brand image effect on Brand attitude and d). Does Brand attitude affects the Brand resonance. The purpose of this study were: a). to know the attributes of brand image building, b). Relation of brand image, brand attitude and brand resonance as brand equity construction and c). The position matrix of notebooks based on the brand image. The model used adapted from Keller (2008). Pre study was conducted to obtain the attributes that are important to consumers by interviewing 10 people with backgrounds notebook vendors, IT workers and students. Attribute the results are then grouped into 8 groups of attributes. Multiple Regression Analysis of the results was found F test result is 0.000 or significant and partial results of each variable, ie: brand, the main specification, specification support and durability demonstrated significant results and other variables are: price, service and features do not show significant results. Results from simple regression analysis of brand attitude on brand resonance shows the results of F test are .000 or significant results. The results demonstrate HP's map position of the best positions on the dimensions of price, brand, design and specifications. Acer is the best on the dimension of features, Toshiba's best on the dimension of durability and serviceability. Asus Notebooks best in the dimension specifications support. Hypothesis test results for H1 and H2 show that the H1 and H2 accepted.